2021
DOI: 10.22159/ijap.2021v13i5.42294
|View full text |Cite
|
Sign up to set email alerts
|

Biocomputational and Pharmacological Analysis of Phytochemicals From Zingiber Officinale (Ginger), Allium Sativum (Garlic), and Murrayakoenigii (Curry Leaf) in Contrast to Type 2-Diabetes

Abstract: Objective: This study was aimed to analyze the inhibitory effect of the flavonoid class of phytochemicals present in ginger (Zingiber Officinale), garlic (Allium sativum), and curry leaf (Murrayakoenigii) against some receptors of type-2 diabetes such as human aldose reductase receptor, mitogen synthase kinase receptor, as well as dipeptidyl peptidase receptor by implementing several in silico analysis techniques. Methods: The 3D structures of the flavonoid class of phytochemicals of all the three plants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…For the hydrophobic bonds, α-mangosteen bound to residues Phe504, Leu517 Val335, Leu 345, and Ile331 via the alkyl and methoxy groups on the side chain of α-mangosteen. This is related to Dermawan et al (2018), who stated that hydrophobic bonds in drug-receptor interactions are very important because they greatly affect the absorption and permeation process of a drug or a compound [24].…”
Section: Tyr341mentioning
confidence: 77%
“…For the hydrophobic bonds, α-mangosteen bound to residues Phe504, Leu517 Val335, Leu 345, and Ile331 via the alkyl and methoxy groups on the side chain of α-mangosteen. This is related to Dermawan et al (2018), who stated that hydrophobic bonds in drug-receptor interactions are very important because they greatly affect the absorption and permeation process of a drug or a compound [24].…”
Section: Tyr341mentioning
confidence: 77%
“…Boswellia serrata, popularly known as Indian frankincense, is a plant indigenous to India and the Middle East that has long been valued for its anti-inflammatory and anti-cancer effects in traditional medicine [11]. Boswellic acids are among the major phytocompounds found in the resin of the Boswellia serrata tree, and research has indicated that they may be useful in preventing cancer by targeting GFRs [20,23]. Hence, we are currently focusing on EGFR, FGFR, ILGFR, PDGFR, and VEGFR targets with Boswellia serrata secondary compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Drug discovery and development can be expedited, making it quicker and more affordable, by identifying the pharmacological and ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) properties of small compounds through in silico investigations. Also, it is possible to find drug candidates with a greater probability of success using in silico techniques, thereby decreasing the possibility of drug failure [20]. The physicochemical properties, drug-likeness properties, and ADMET properties of the small molecules were evaluated using the ADMETlab 2.0 webserver (https://admetmesh.scbdd.com/) [21].…”
Section: Pharmacological Studiesmentioning
confidence: 99%
“…The first step taken was using the protein data bank database (https://www.rcsb.org/) as the source to download the receptors in (.pdb) format [10][11][12][13]. Afterwards, the preparation of each receptor was carried out by separating it from the complexed lead compounds using Discovery Studio Visualizer software.…”
Section: Validation Using Molecular Docking Methodsmentioning
confidence: 99%